Application research of a structural topology optimization method based on a bionic principle. Issue 10 (3rd October 2021) - Zhong, Yuhai; Feng, Huashan; Wang, Runxiao
Abstract : From the perspective of bionics, a structural topology optimization method combining a bone remodelling algorithm and real engineering requirements is proposed. Through joint simulation using MATLAB and Ansys, this method uses explicit physical concepts and efficient computer solving capabilities, which makes it highly practical and simple. The effectiveness and feasibility of the method are verified by comparing topology optimizations performed on four classical examples and the optimized results from the 99 lines of topology optimization code. Next, some key parameters of the method are discussed in depth, laying the foundation for a deeper understanding and application of the method. The purpose of this article is to introduce a bionic theory into the field of topology optimization by implementing an easy-to-use and extensible numerical algorithm to promote the development of this technology, so that it can better realize its engineering value.